Densidade e caracterização genotípica das linhagens de ferrobactérias isoladas de água de poços rasos em Cuiabá - Mato Grosso - Ramos, Pâmila Nayana Ferreira (2015)
The use of shallow wells as water source is a common practice worldwide for the quality of aquifers are suitable for various uses, mainly for human consumption. However, pollution of this resource can occur in various forms, such as bacterial contamination, specifically by Iron Bacteria. Therefore, this study aims to analyze the genotypic profile of Iron Bacteria isolated from water from shallow wells in the neighborhood Stone Ninety, Cuiaba-MT. The water sampling in the sampling points were held in November 2013 (the beginning of the rainy season) and January 2014 (regular rainfall), in the neighborhood Stone Ninety in Cuiaba, as sampler using the manual type bailer. After quantification of Iron Bacteria, via selective medium, were isolated for DNA extraction and genotypic characterization using BOX-PCR primer. From the product of BOX-PCR electrophoresis, gels were generated which account sixteen seventeen points for each sampling period. The similarity of the samples was determined by binary matrices presence and absence for each of the analysis points, depending on the position occupied bands in the gel. From the dissimilarity matrix were grouped into UPGMA dendrograms and Jaccard similarity analysis (2%) to the percentage of similarity among isolates of each point. To iron metal analyzes were performed two collections into two distinct periods points P2, P7, P10 and P16 showed concentrations above the Maximum Allowable Values for human consumption. For microbiological analyzes all samples were contaminated by Iron Bacteria. Through dendrograms dissimilarity, it was noticed that 10.9% of the isolates obtained a similarity greater than 70%, which leads to the inference that 89.1% of the isolates showed genetic diversity.